Association of Obesity, Sarcopenia, and Sarcopenic Obesity With Hypertension in Adults: A Cross-Sectional Study From Ravansar, Iran During 2014-2017 - Yahya Pasdar; Yahya Pasdar; Mitra Darbandi; Shahab Rezaeian; Farid Najafi; Farid Najafi; Behrooz Hamzeh; Behrooz Hamzeh; Amir Bagheri; Amir Bagheri (Frontiers Media S.A., 2022)
Background and AimsHypertension may lead to disability and death by increasing the risk of cardiovascular disease, kidney failure, and dementia. This study aimed to determine the association between obesity, sarcopenia and sarcopenic obesity, and hypertension in adults resident in Ravansar, a city in the west of Iran.MethodsThis cross-sectional study was conducted on 4,021 subjects from the baseline data of the Ravansar Non-Communicable Disease (RaNCD) cohort study, in the west region of Iran, from October 2014 up to February 2017. Body composition was categorized into obese, sarcopenia, sarcopenic obese, and normal based on measurements of muscle strength, skeletal muscle mass, and waist circumference. Univariate and multiple logistic regression models were used to examine the relationships, using the STATA 15 software.ResultsThe mean age of the participant was 47.9 years (SD: 8.4), the body mass index (BMI) was 26.84 kg/m2 (SD: 4.44), and the prevalence of hypertension was 15.12%. The prevalence of obesity, sarcopenia, and sarcopenic obesity were 24.37, 22.01, and 6.91%, respectively. Body composition groups had significant differences in age, total calorie intake, BMI, skeletal muscle mass, and muscle strength (P-value ≤ 0.001). In crude model, the obese (OR = 2.64; 95% CI: 2.11-3.30), sarcopenic (OR = 2.45; 95% CI: 1.94-3.08), and sarcopenic obese (OR = 3.83; 95% CI: 2.81-5.22) groups had a higher odds of hypertension. However, in adjusted models, only the obese group had a higher likelihood of hypertension (OR = 2.18; 95% CI: 1.70-2.80).ConclusionThis study showed that obesity was associated with hypertension, whereas sarcopenia and sarcopenic obesity had no significant relationship with hypertension.